Semantics and Pragmatics of Combinations «Indefinite Pronoun + Adjective» - Gazarova, Diana (Bulletin of Yerevan University H: Russian Philology, 2024)
The article examines the features of the functioning of indefinite pronouns with -то in combination with adjectives. In these combinations, pronouns express relative, partial indefiniteness. The article presents three types of combinations: 1) combinations of indefinite substantive pronouns with adjectives (что-то ужасное); 2) combinations of indefinite adjective pronouns with attributive adjectives (какой-то новый документ) and 3) combinations of indefinite adjective pronouns with predicate adjectives (Она сегодня какая-то грустная). In the first and second types of combinations, indefiniteness is weakened due to the fact that the speaker is able to name the signs of the described phenomenon, but the phenomenon itself remains unidentified. The boundaries of indefiniteness are narrowed while the indefiniteness of the referent remains unchanged. In the third type of combinations, the speaker is not sure of the accuracy of the quality’s nomination itself; pronouns act as markers of indefiniteness in the manifestation of a definite quality. Basically, in such cases, combinations of indefinite pronouns are possible with adjectives that contain in their meaning a deviation from the norm and from the standard. Indefinite pronouns indicate a non-prototypical manifestation of a quality, that’s why combinations of indefinite pronouns with adjectives that have in their meaning a sense of non-standardity and unusualness are so common. These are mostly negative contexts (Он вообще какой-то странный; Ты сегодня какой-то злой). In all three types of combinations of indefinite pronouns with adjectives indefinite pronouns indicate the pragmatic meaning of the statement, partial indefiniteness, when the indefiniteness is specified. In the first two types the referent is indefinite, in the third type the quality of a definite referent is indefinite.